Identification, Characterization and Full-Length Sequence Analysis of a Novel Polerovirus Associated with Wheat Leaf Yellowing Disease - Zhang, Peipei; Liu, Yan; Liu, Wenwen; Cao, Mengji; Massart, Sebastien; Wang, Xifeng (Frontiers in Microbiology, 2017)
To identify the pathogens responsible for leaf yellowing symptoms on wheat samples collected from Jinan, China, we tested for the presence of three known barley/wheat yellow dwarf viruses (BYDV-GAV, -PAV, WYDV-GPV) (most likely pathogens) using RT-PCR. A sample that tested negative for the three viruses was selected for small RNA sequencing. Twenty-five million sequences were generated, among which 5% were of viral origin. A novel polerovirus was discovered and temporarily named wheat leaf yellowing-associated virus (WLYaV). The full genome of WLYaV corresponds to 5 772 nucleotides (nt), with six AUG-initiated open reading frames, one non-AUG-initiated open reading frame and three untranslated regions, showing typical features of the family Luteoviridae. Sequence comparison and phylogenetic analyses suggested that WLYaV had the closest relationship with sugarcane yellow leaf virus (ScYLV), but the identities of full genomic nucleotides and deduced amino acid sequence of coat protein (CP) were 64.9% and 86.2%, respectively, below the species demarcation thresholds (90%) in the family Luteoviridae. Furthermore, agroinoculation of Nicotiana benthamiana leaves with a cDNA clone of WLYaV caused yellowing symptoms on the plant. Our study adds a new polerovirus that is associated with wheat leaf yellowing disease, which would help to identify and control pathogens of wheat.